2012
DOI: 10.1002/anie.201108015
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Human α2‐Macroglobulin Reveals a Unique Molecular Cage

Abstract: I'm your Venus: The crystal structure of the human methylamine‐induced form of α2‐macroglobulin (α2M) shows its large central cavity can accommodate two medium‐sized proteinases (see structure, front part clipped off to better show central cavity). Twelve major entrances provide access for small substrates to the cavity and the still‐active trapped “prey”. The structure unveils the molecular basis of the unique “venus flytrap” mechanism of α2M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 24 publications
7
80
0
1
Order By: Relevance
“…1b). Previous studies with human and E. coli A2M have shown that reaction with methylamine inactivates the thioester and causes a major conformational change in the eukaryotic variant 5,19,32,33,[37][38][39] . To address the issue of a potential conformational change in a bacterial A2M on activation, we solved the crystal structure of methylamine-treated Sa-A2M.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b). Previous studies with human and E. coli A2M have shown that reaction with methylamine inactivates the thioester and causes a major conformational change in the eukaryotic variant 5,19,32,33,[37][38][39] . To address the issue of a potential conformational change in a bacterial A2M on activation, we solved the crystal structure of methylamine-treated Sa-A2M.…”
Section: Resultsmentioning
confidence: 99%
“…Protease entrapment occurs through a 'Venus flytrap mechanism' 4,5 involving proteolytic cleavage of the recognized bait region, followed by a large conformational change that blocks the target protease within a cage-like complex. Exposure of the highly reactive thioester site (CXEQ), which associates covalently to the protease, prevents its escape.…”
mentioning
confidence: 99%
“…2b) of the three vertebrate complement factors C3–C5 and Ag TEP1 (Janssen et al 2005; Fredslund et al 2006, 2008; Baxter et al 2007; Laursen et al 2010), and the post-activation state (Fig. 2c) of C3 and C5 (C3b, C5b), and MeNH 2 -treated A 2 M (A 2 M-MeNH 2 ) (Janssen et al 2006; Wiesmann et al 2006; Hadders et al 2012; Marrero et al 2012). Distortion of the quaternary structure, such as the pre-activation state of Ag TEP1 and disorder of RBD in the post-activation state of A 2 M, is discussed below.…”
Section: Inter-domain Interactions and Conformational Changementioning
confidence: 99%
“…MG7 contacts both CUB and MG8 and the whole α chain sits on top of the β-ring, the MG2–MG6 dimer contacting the TED-CUB-MG8 superdomain while MG3 contacts MG7. There is currently no A 2 M crystal structure with an intact thioester bond, but flexible modeling of SAXS and EM data for tetrameric human A 2 M and monomeric E. coli A 2 M (ECAM) support a similar domain arrangement to that of complement and Ag TEP1 (Marrero et al 2012; Neves et al 2012). …”
Section: Inter-domain Interactions and Conformational Changementioning
confidence: 99%
See 1 more Smart Citation